Modeling of enhanced ultraviolet (UV) band detector using Electrostatic Field Effect (ESF) - Bablu K. Ghosh (Universiti Malaysia Sabah, 2015)
This project is based on the modeling of Si UV detector by a novel technique to improve its performance. Using linear junction model, doping profile and reverse biased voltage are found to be effective on generation rate, junction capacitance, speed and operating bandwidth. It appears that lower n-doping (body) and higher limit of reverse voltage make it faster response but optimization of doping and reverse biasing are found important to control the transit time. The different passivation layer with harmonized anti reflection layer combination impact are also studied. Different materials such as aluminum oxide (Al2O3), zinc oxide (ZnO), silicon nitride (Si3N4), silicon dioxide (SiO2) and silicon carbide (SiC) and emitter layers effect on photo response have been assessed. By matching the band gap energy and the thickness of those materials, UV absorption inside the active layer can be controlled and eventually photo response is found to be optimized. In this aspect combination of SiO2 and Si3N4 harmonized layers is found promising. Designing PN, P+N, P+iN, NP N+P and N+iP detectors by using harmonized layers, the photo response, quantum efficiency and load/cathode current modeling are also done. A model to evaluate the output current of the cSi W photo detector is performed. The variation of output current as a function of capacitance, response time, junction depth and doping concentration has been analyzed using the model. So such novel techniques for modeling of low cost high photo response and sensitivity UV detector by using cSi are successfully performed.